Molecular Detection of Taura Syndrome Virus Infections in White Shrimp (Litopenaeus vannamei) and Giant Prawn (Macrobrachium rosenbergii) - Fariha Willisiani; Nur Rohmah; Irma Nur Rahmawati; Nastiti Wijayanti (Jurnal Sain Veteriner, 2013)
Abstract Giant prawn (Macrobrachium rosenbergii) and vaname shrimp (Litopenaeus vannamei) are types of shrimp that became excellent commodities in the fisheries sector. However, one of the obstacles in the vaname shrimp aquaculture is a disease caused by the infection of Taura Syndrome Virus (TSV). One of the consequence of raising the vaname shrimp in Indonesia is the possibility of spreading TSV infection in another shrimp species. TSV infection in giant prawns in Indonesia has not been reported. The aims of this study were: 1. To determine the resistance of giant prawns toward TSV infection and 2. To detect molecularly using RT-PCR technique the presence of viruses TSV on vaname shrimp or giant prawns infected with 3 different doses (0.05 ml; 0.10 ml and 0.15 ml) of TSV inoculum using a pair of specific primers for TSV 9992F (5'-AAG CTT GCG TAG ACA GCC-3') and 9195R (5'-TCA AGA ATG GCT TCC TGG-3'). The research results showed that vaname shrimp mortality infected by 0.05 ml; 0.10 ml and 0.15 ml TSV inoculums were 14.28%, 42.86%, and 57.14%, respectively. Whereas the giant prawns mortality that were infected using the same dose of TSV inoculums were 0%, 8.33%, and 8.33%, respectively. Positive result was detected molecularly only from haemolymph of vaname shrimp infected using 0.15 ml of TSV inoculum. On the other hand, positive results were detected in pleopod and the gill of vaname shrimp infected using 0.05 ml; 0.10 ml or 0.15 ml of TSV inoculums. In giant prawns, infection using 3 different doses of TSV inoculums causes negative result molecularly. Based on all of the facts, it can be concluded that, giant prawns has the higher resistance to TSV infection than that of vaname shrimp.